Pelayanan Rehabilitiasi Sosial Bagi Penyalahguna Narkoba Di Yayasan Cahaya Putra Selatan Palembang - Bintang Meisy Pramesti; Neni Noviza; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2024)
Drug abuse is a serious problem that threatens young people throughout the world, including in Indonesia. This misuse can cause various negative impacts such as health problems, financial and legal problems. Cahaya Putra Selatan Foundation exists as a rehabilitation institution that aims to help victims of drug abuse recover and return to their role in society. This research aims to determine social rehabilitation services for drug abusers and to determine the supporting and inhibiting factors in social rehabilitation services for drug abusers. To examine the research data, data collection was used using research methods in the form of observation, interviews, documentation. After the data is collected, it will be presented through data reduction and analyzed using qualitative descriptive presentation. The results of this research show that social rehabilitation services at the Cahaya Putra Selatan Foundation in Palembang have been running quite well. The methods used are therapeutic community (TC) and a religious approach. Strong supporting factors in social rehabilitation services, such as therapy, facilities and effective collaborative relationships. The inhibiting factors are lack of family support and community support.